Zasady rozbudowywania frazy nominalnej w języku niemieckim i polskim - Kubacki, Artur Dariusz (Investigationes Linguisticae, 2009)
The aim of the article is to present and examine the rules for the extension of nominal phrases in German and Polish. The analysis concerns the patterns of the extension of German and Polish attributes according to Schatte, Jodłowski, Weinrich, and also according to connotation (valency) principles. On the basis of the German deverbative nouns with the suffix -ung found in an arbitrarily selected legal and economic text, the author shows how connotations are inherited.